Fikih Perempuan Tentang Aurat dan Busana Muslimah - Eliza, Mona; Abbas, Afifi Fauzi (IDRIS Darulfunun Institute, 2023)
In Islam, understanding the aurat and ethics of Muslim women's clothing is very important, reflecting compliance with religious teachings, the identity and dignity of a Muslim woman. Aurat, which must be covered from non-mahram views in accordance with the Koran and Sunnah, and Muslim dress, which emphasizes fulfilling the requirements of awrah, is not only a religious requirement but also a way to maintain purity and avoid slander. This awareness helps shape the dignified character and personality of Muslim women, and strengthens their identity in society, enabling them to appear elegant without sacrificing religious values. This understanding also supports the creation of a harmonious social environment that respects diversity. Therefore, understanding the importance of aurat and Muslim dress is not only in worship and religious observance, but also in the formation of social identity and contribution to a mutually respectful society. This shows how Islam moderates religious understanding with respect for oneself and positive social development of society.